Low velocity impact response of laminated textile coir-aramids/epoxy hybrid composites subjected to transverse penetration loading - Abdul Rashid, Azrin Hani (2015)
The hybrid of natural and synthetic fibres in a composite system has gained interest in research field due to the environmental consciousness. Coir natural fibre has been found to have a high potential as impact resistance, in which brittle fibre helps to spread the impact energy over a wider area. The focus of the study is to determine if any improvement in impact response exists as a result of combining high performance Kevlar synthetic fibre and coir natural fibre in a specified laminated stacking sequence. In this research, quasi-static experiments were conducted at the speed of 1.25 mm/s, and low velocity impact tests were conducted using a 12.7 mm hemispherical impactor at the speed varying from 5 m/s to 17 m/s. Matlab software was used for curve fitting of the raw data, whereas ANOVA and DOE via Minitab software were employed for statistical examination to support the results. The area of the damaged composite was evaluated using the image analysis technique by Matlab image processing tool. The morphology analysis of the impact fractured surfaces was also observed by SEM. At the beginning stage, the optimum impact responses of coir epoxy composites subjected to different reinforcement architecture, composite manufacturing method, fabric modification and fabric density were determined. The findings showed that the impact responses could be effectively controlled by varying material parameters. Coir fibre in the form of woven structure with dense structure, treated using 6% of NaOH solution and manufactured by compression moulding method was found to be effective in absorbing and propagating impact energy. The respective coir was then used in hybrid laminates. Coir/Kevlar epoxy hybrid composites consisted of three interply laminates layers at six different stacking configurations were developed. It was observed that the hybrid composite (two coir layers and one Kevlar layer) had equivalent specific total energy absorption as 100% Kevlar laminate (at three layers). It can be concluded that the hybrid of coir/Kevlar-epoxy laminated composites had shown an improved in impact response. It also provides cost-effective materials and contributes towards green technology which will be of great benefit to the industry and community.